Health Disparities: A Perspective on Internal Migration and Health Behavior in Sudan - Mahmoud Ali Fadlallah; Indrajit Pal; Joyee S. Chatterjee (Ubiquity Press, 2020)
Background: Natural hazards, poor socio-economic conditions, low literacy levels, and long-standing conflicts affect traditional gold miners in Sudan and contribute to multiple health vulnerabilities. An extensive survey reveals differential health risk among internal migrant miners leading to short-, medium-, and long-term health consequences and disparities. The need to identify determinants of health behavior and limited prior research on internal migrants involved in traditional gold mining in Sudan motivated this research. Objective: To investigate potential health disparities between internal migrant workers participating in traditional gold mining and their local counterparts. Methods: Questionnaires on socio-demographic and health status in the Abideya area in the River Nile state of Sudan were administered to 211 miners. Composite score variables were devised based on existing literature and data for assessment of underlying risk determinants for the miners' vulnerability (migrants and non-migrants). Six new composite variables were constructed and subjected to analysis by immigration status. Findings: There are disparities in drivers of health behavior related to the immigration status of traditional gold miners. Access to water, sanitation, and hygiene services are common determinants for the health behavior of both internal migrant miners (p < 0.001) and their local counterparts (p < 0.001). However, knowledge (p < 0.05) and perception (p < 0.05) are additional critical determinants for the health behavior of local miners, while education (secondary, p < 0.01) is an additional modifier for the immigrants' health behavior. Conclusions: The outcomes of this field-based research suggest increased awareness and risk perceptions among migrants could improve health-related behaviors. The study advocates for policymaking and implementation of health programs at all levels to reduce health disparities between migrants and non-migrants, improving the health status of the entire community.